Pengaruh Penghargaan Finansial, Lingkungan Kerja, Pertimbangan Pasar Kerja Terhadap Minat Menjadi Akuntan Pemerintah (Studi Kasus Pada Mahasiswa Akuntansi S1 Universitas Negeri Padang) - Wella Fira Afri Yanti; Annisa Annisa (CV. Ulil Albab Corp, 2023)
The purpose of this study was to provide empirical evidence about the effect of financial rewards, work environment, and labor market considerations on the intention to become a government accountant (a case study on an undergraduate accounting student at Padang State University). This study used a quantitative research method. Data obtained from primary data by distributing questionnaires using incidental sampling techniques and using the slovin formula. The population in this study were active students of the Padang State University Bachelor of Accounting study program in 2018/2020 using 78 samples in this study consisting of Bachelor of Accounting students at Padang State University. The results of this study produce a coefficient of determination which indicates that the influence of financial rewards, work environment and labor market considerations have an effect on interest in becoming a government accountant by 52.1% while 47.9% is influenced by other variables not examined in this study.